Strength Assessment of an Improved Design of a Tank Container under Operating Conditions - Panchenko, Sergii; Gerlici, Juraj; Vatulia, Glib; Lovska, Alyona; Rybin, Andrij; Kravchenko, Oleksandr (Communications - Scientific Letters of the University of Zilina, 2023)
The publication presents the results of research into the strength of an improved tank container. The tare of a tank container can be reduced through application of composite material for the tank. In this case its mass can be 46% lower than that of a metal tank. The strength of the tank was calculated by computer simulation. The maximum stress occurs in its lower part and is about 295 MPa.
Keywords: tank container; improvement construction; dynamic load; construction strength; container transportation